2018
DOI: 10.48550/arxiv.1805.03666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Normal generators for mapping class groups are abundant

Abstract: We provide a simple criterion for an element of the mapping class group of a closed surface to have normal closure equal to the whole mapping class group. We apply this to show that every nontrivial periodic mapping class that is not a hyperelliptic involution is a normal generator for the mapping class group when the genus is at least 3. We also give many examples of pseudo-Anosov normal generators, answering a question of D. D. Long. In fact we show that every pseudo-Anosov mapping class with stretch factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Further, any Type 2 cyclic action can be constructed from certain compatibilities on irreducible Type 1 actions [19,Theorem 2.24]. These results allow us to take an alternative approach which bypasses the usages of [14,Lemma 3.2]. However, we will use the well-suited curve criterion from [14].…”
Section: Normal Closure Of Pseudo-periodic Mapping Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, any Type 2 cyclic action can be constructed from certain compatibilities on irreducible Type 1 actions [19,Theorem 2.24]. These results allow us to take an alternative approach which bypasses the usages of [14,Lemma 3.2]. However, we will use the well-suited curve criterion from [14].…”
Section: Normal Closure Of Pseudo-periodic Mapping Classesmentioning
confidence: 99%
“…These results allow us to take an alternative approach which bypasses the usages of [14,Lemma 3.2]. However, we will use the well-suited curve criterion from [14].…”
Section: Normal Closure Of Pseudo-periodic Mapping Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further observation on reducible mapping classes gives an analogous criterion for them as in [LM18]. Let f ∈ Mod(S) be reducible with maximal invariant multicurve γ and ℓ T (f ) > 0.…”
Section: Mapping Classes With Small Asymptotic Translation Lengthsmentioning
confidence: 99%
“…Question 1.1 is motivated by a work of Lanier-Margalit [LM18] which showed that a pseudo-Anosov element with small minimal translation length normally generates the mapping class group where "small" means less than 1 2 log 2. The question is of course open-ended since it does not specify what we mean by "small" and "obvious counterexample".…”
Section: Introductionmentioning
confidence: 99%